Comparison of HbA1c, blood pressure, and cholesterol (ABC) control in type 2 diabetes attending general medical clinics and specialist diabetes clinics in Thailand. Issue 2 (May 2015) - Sieng, Sokha; Thinkamrop, Bandit; Laohasiriwong, Wongsa; Hurst, Cameron
Abstract Aims The aim of this study was to compare the achievement of clinical targets for patients with type 2 diabetes mellitus (T2DM) in general medical clinics (GMCs) and specialist diabetes clinics (SDCs) for different hospital types (regional, provincial and community) in Thailand. Methods We used the medical records of patients (n = 26, 860) with T2DM from 595 hospitals (26 regional, 70 provincial and 499 community) across all 77 provinces in Thailand. Generalized linear mixed models were used to conduct multi-level modeling to evaluate the achievement of individual outcomes (A – glycated hemoglobin (HbA1c) <7.0% (53 mmol/mol), B – Blood Pressure (BP) <140/80 mmHg and C – LDL-Cholesterol <100 mg/dL) and aggregated outcomes (AllABC – achieved all three of the targets, AnyABC – achieved at least one target, ABCcount – the number of targets achieved: 0, 1, 2 or 3). Results Neither clinic types (SDCs or GMCs) were consistency superior across all hospital types. For regional hospitals, SDCs were associated with higher odds of achieving BP, AnyABC, and ABCcount (OR = 1.55, 95%CI: 1.25–1.92, p < 0.001; OR = 1.35, 95%CI: 1.02–1.79; p = 0.04; RR = 1.10, 95%CI: 1.01–1.20, p = 0.03, respectively). For provincial hospitals, SDCs exhibited higher achievement of BP and LDL-C (OR = 1.52, 95%CI: 1.23–1.87, p < 0.001; OR = 1.28, 95%CI: 1.04–1.58, p = 0.02, respectively). For community hospitals, however GMCs demonstrated higher achievement of BP and AnyABC (OR = 0.81, 95%CI: 0.67–0.98, p = 0.03; OR = 0.74, 95%CI: 0.56–0.97, p = 0.03, respectively). Conclusions In larger (regional and provincial) hospitals, SDCs outperform GMCs in several (but not all) clinical targets. In contrast, in community hospital, where most patients with T2DM are serviced, GMCs were shown to have superior performance.